Temporal incidence of Leifsonia xyli subsp. xyli in sugarcane propagating materials of Brazilian cultivars. (February 2020) - Urashima, A.S.; Silva, M.F.; Coraini, N.F.; Gazaffi, Rodrigo
Abstract: Re-establishment of a new sugarcane field takes place in 15–20% of the cultivated area of the Brazilian sugar industry annually, a territory that covered 10.1 million hectares in Brazil in 2018. Ratoon stunt (RSD), caused by Leifsonia xyli subsp. xyli (Lxx), is one systemic disease transmitted through contaminated propagating materials. Clean seedcane is especially important for RSD because infected seedcane is the primary inoculum to new sugarcane fields. Therefore, the objective of this work was to examine the temporal incidence of Lxx in prospective fields that provide propagative materials for nursery formation of five most employed cultivars for re-establishment of a new sugarcane field in the Center-South region of Brazil during the 2013–2018 period. Sugarcane sap from 100 stalks per field was sent by growers for routine diagnostic tests and analyzed by dot-blot immunoassay. Our data showed a high Lxx infection levels in all cultivars with an average of 40.2% in the period of study with rising tendency of Lxx contamination in prospective fields because samples of 2018 had significant higher incidence, June and July were the months with highest positive samples. Moreover, all cultivars were highly susceptible to RSD, demonstrating the potential damage to the Brazilian sugarcane industry and the need for the industry to adopt more strict sanitation practices for sugarcane nursery formation. Highlights: High prevalence of ratoon stunt in samples from all five sugarcane cultivars. The average disease incidence during 2013-18 was 40.2%. Samples from 2018 had significant higher disease incidence. June and July were the months with highest positive samples. All sugarcane cultivars were highly susceptible to ratoon stunt.